Experimental infection by Yersinia ruckeri O1 biotype 2 induces brain lesions and neurological signs in rainbow trout (Oncorhynchus mykiss). Issue 3 (17th November 2017) - Strøm, H K; Ohtani, M; Nowak, B; Boutrup, T S; Jones, B; Raida, M K; Bojesen, A M
Abstract: Pathological manifestations in rainbow trout ( Oncorhynchus mykiss ) following experimental waterborne infection with Yersinia ruckeri serotype O1 biotype 2 (strain 07111224) were investigated. Rainbow trout were exposed to 8 × 10 7  CFU/ml of Y. ruckeri by bath for 6 hr, and mortality was then monitored for 22 days post‐infection (dpi). Organs were sampled at 3 dpi and also from moribund fish showing signs of severe systemic infection such as bleeding, exophthalmia or erratic swimming behaviour. Y. ruckeri was observed in the meninges and diencephalon of the brain, and lamina propria of olfactory organ at 3 dpi. At 12 dpi, Y. ruckeri had spread throughout the brain including cranial connective tissues and ventricles and the infection was associated with haemorrhages and an infiltration with leucocytes. Y. ruckeri infection and associated with leucocyte infiltration were observed at 13 dpi. In conclusion, Y. ruckeri strain 07111224 causes encephalitis in the acute phase of infection, which could explain why Y. ruckeri ‐affected fish show exophthalmia and erratic swimming known as signs of ERM.